2019
DOI: 10.1021/acsomega.9b01879
|View full text |Cite
|
Sign up to set email alerts
|

Residue Network Involved in the Allosteric Regulation of Cystathionine β-Synthase Domain-Containing Pyrophosphatase by Adenine Nucleotides

Abstract: Inorganic pyrophosphatase containing regulatory cystathionine β-synthase (CBS) domains (CBS-PPase) is inhibited by adenosine monophosphate (AMP) and adenosine diphosphate and activated by adenosine triphosphate (ATP) and diadenosine polyphosphates; mononucleotide binding to CBS domains and substrate binding to catalytic domains are characterized by positive cooperativity. This behavior implies three pathways for regulatory signal transduction — between regulatory and active sites, between two active sites, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…AMP binding allosterically activates AMPK and protects AMPK from dephosphorylation [ 54 , 55 ]. Ultimately, AMP binding initiates a conformational rearrangement of AMPKɑ in which the catalytic T172 within the T-loop of the kinase domain becomes accessible to upstream AMPK kinases [ 56 ]. Although most investigations of AMPK function and regulation have focused on AMPKɑ and AMPKγ subunits, AMPKβ is necessary for interactions involving carbohydrates [ 57 ], and is post-translationally modified to upregulate or downregulate the enzymatic activity of AMPKɑ [ 58 ].…”
Section: Investigating Lkb1-strad-mo25 Activitymentioning
confidence: 99%
“…AMP binding allosterically activates AMPK and protects AMPK from dephosphorylation [ 54 , 55 ]. Ultimately, AMP binding initiates a conformational rearrangement of AMPKɑ in which the catalytic T172 within the T-loop of the kinase domain becomes accessible to upstream AMPK kinases [ 56 ]. Although most investigations of AMPK function and regulation have focused on AMPKɑ and AMPKγ subunits, AMPKβ is necessary for interactions involving carbohydrates [ 57 ], and is post-translationally modified to upregulate or downregulate the enzymatic activity of AMPKɑ [ 58 ].…”
Section: Investigating Lkb1-strad-mo25 Activitymentioning
confidence: 99%
“…However, the identity of the structural element that mediates the AMP signal can only be conjectured. Earlier mutagenesis studies of dhPPase have identified two interacting elements, helix α1 of CBS2 domain and the loop formed by residues 310-323 in the DHH domain, among the best candidates for signal transmission from the regulatory site to the catalytic DHH domain [37]. Notably, an Ala substitution for the highly conserved Asn312 in this loop reversed the effect of ATP on dhPPase from activation to inhibition [37].…”
Section: Mechanism Of Regulationmentioning
confidence: 99%
“…Earlier mutagenesis studies of dhPPase have identified two interacting elements, helix α1 of CBS2 domain and the loop formed by residues 310-323 in the DHH domain, among the best candidates for signal transmission from the regulatory site to the catalytic DHH domain [37]. Notably, an Ala substitution for the highly conserved Asn312 in this loop reversed the effect of ATP on dhPPase from activation to inhibition [37]. Furthermore, replacement of Arg168 in the highly conserved RyR motif of Moorella thermoacetica CBS-PPase (corresponding to Arg276 of dhPPase) weakened AMP binding and reversed its effect from inhibition to activation [38].…”
Section: Mechanism Of Regulationmentioning
confidence: 99%
“…CBS-PPase provides a good model for studying CBS domain-mediated regulation because it is easily accessible and stable, is differentially regulated by adenosine phosphates, including cell alarmones diadenosine polyphosphates, and its activity can be conveniently and precisely measured. In recent site-directed mutagenesis studies of dhPPase, we identified Arg276 and Arg295 in the CBS2 and Asn312 and Arg334 in DHH domains as having crucial roles in kinetic cooperativity (active site interaction) [14,15]. Another important finding was that replacement of Arg295 or Asn312 by alanine reversed the effect of ATP from activation to inhibition [15].…”
Section: Introductionmentioning
confidence: 97%